1986
DOI: 10.1073/pnas.83.12.4529
|View full text |Cite
|
Sign up to set email alerts
|

Successful liver allografts in mice by combination with allogeneic bone marrow transplantation.

Abstract: Successful liver allografts were established by combination with allogeneic bone marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…10,11 However, this method was not applicable to humans because of lethal levels of irradiation, and allogeneic BMT in humans has several other problems such as GvHD. As described here, we have recently found that 'PV-BMT' is better than 'IV-BMT'.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, this method was not applicable to humans because of lethal levels of irradiation, and allogeneic BMT in humans has several other problems such as GvHD. As described here, we have recently found that 'PV-BMT' is better than 'IV-BMT'.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of tolerance against the transplanted liver after OLT in mice [14], primates [21], and humans [12,171. Several studies in humans show enhanced allograft survival [ 19,201 when repeated BM infusions are given after allograft transplantation or at the time of OLT.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that the combination of organ allografts and IBM-BMT from the same donors was the most effective strategy to prevent the rejection of organ allografts, since the radiation dose could be reduced to 4Gy x 2 in skin allografts [76,77]. In addition, we have found that IBM-BMT is applicable to allografts of other organs and tissues in rats and mice, such as pancreas islets, legs, lungs, heart and ovary [78][79][80][81][82][83] .…”
Section: Intra Bone Marrow-bmt (Ibm-bmt) For Metabolic Disorders and mentioning
confidence: 99%